Characterisation of plasmids conferring ampicillin resistance in South African isolates of haemophilus ducreyi - Leong, May-Yong Geraldine (My University, 1996)
Fifty-two strains of Haemophilus ducreyi from various geographic regions of southern Africa (Botswana, Lesotho, Namibia, Gauteng, Natal and Transkei) isolated between 1988 to 1994 were tested for susceptibilities to five antimicrobial agents and characterized according to their plasmid content and ampicillin- resistance genes.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science (medicine).' Johannesburg 1996
Keywords: Plasmids; Ampicillin; Haemophilus ducreyi; Anti-Infective Agents